Lives and Times of Great Pioneers in Chemistry. (Lavoisier to Sanger) Von C. N. R. Rao und Indumati Rao. (11th April 2016) - Labinger, Jay A.
Abstract : World Scientific Publishing, Singapore 2016. 324 S., geb., 38.00 £.—ISBN 978‐9814689052